Free Space Optical Communication - Kaushal, Hemani; Jain, V.K.; Kar, Subrat; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2017)
This book provides an in-depth understanding of free space optical (FSO) communication with a particular emphasis on optical beam propagation through atmospheric turbulence. The book is structured in such a way that it provides a basic framework for the beginners and also gives a concise description from a designer's perspective. The book provides an exposure to FSO technology, fundamental limitations, design methodologies, system trade-offs, acquisition, tracking and pointing (ATP) techniques and link-feasibility analysis. The contents of this book will be of interest to professionals and researchers alike. The book may also be used as a textbook for engineering coursework and professional training.
Chapter 1: Overview of Wireless Optical Communication Systems -- Chapter 2: Free Space Optical Channel Models -- Chapter 3: FSO System Modules and Design Issues -- Chapter 4: Acquisition, Tracking and Pointing -- Chapter 5: BER Performance of FSO System -- Chapter 6: Link Performance Improvement Techniques -- Chapter 7: Link Feasibility Study.
Keywords: Telecommunication; Signal processing; Microwaves, RF Engineering and Optical Communications; Communications Engineering, Networks; Signal, Speech and Image Processing